Hostile acts : U.S. policy in Costa Rica in the 1980s - Honey, Martha (University Press of Florida, 1994)
To Martha Honey, "hostile acts" is shorthand for the nature of U.S. policies in Costa Rica during the last decade. In this book she combines extensive academic research with her firsthand experiences as a journalist covering major portions of the Iran-contra scandal to weave together the story of how the Reagan and Bush administrations undermined Central America's model democracy. Until 1980 Washington paid little attention while Costa Rica quietly developed a benign, quasi-socialist form of government that combined respect for human rights with the goal of achieving economic equality. Then, Honey writes, the new Reagan administration decided that Costa Rica would be important in the war against the Sandinistas in Nicaragua. Over the next few years, the United States poured huge quantities of economic aid into the country and also covertly trained and equipped contra rebel forces to wage war against the Sandinistas from bases in northern Costa Rica
Keywords: United States -- Foreign relations -- Costa Rica.; Costa Rica -- Foreign relations -- United States.; États-Unis -- Relations extérieures -- Costa Rica.; Costa Rica -- Relations extérieures -- États-Unis.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Diplomatic relations; Costa Rica; United States; Außenpolitik; USA; Geschichte 1980-1989.